NEMU–ANG, A NEW MUSICAL COMPOSITION - Santosa, Hendra; Darmawan, I Komang Werdi; Hartini, Ni Putu (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2024)
Nemu-Ang is an innovative Karawitan musical composition. The background of the musical artwork is from the phenomenon of appreciate the melody, which currently doesn't exist in almost every musical artwork. The main reason for that is that the lay public can't enjoy the work. This phenomenon inspired Karawitan's composition with the medium of the Gamelan Singapraga. This Karawitan music composition takes the object of honey as a central object because this honey has a multitude of benefits and a sweet taste that stands out, so this focuses on aspects of how honey is produced and the taste of honey itself. Nemu-Ang's innovative form of musical composition uses rhythm, melody, and harmonization from the Singapraga Gamelan to have a sweet taste like honey and the process of making it. The method for producing this work is Panca Stithi Ngawi Sani by Prof. Dr. I Wayan Dibia, and it is very easy to understand for ordinary people who want to create art. This method includes the ngawirasa (find the inspiration), ngawacak (object exploration), ngarencana (conception of the object), ngawangun (execution of the concept), ngebah (presentation/performed the artwork). Based on the results of applying this method, Nemu-Ang's work was very effective, and the work was realized as it should have a duration of 11 minutes. In the future, this work can be enjoyed by the wider community to become an inspiration for further musical works.